1998
DOI: 10.1159/000015856
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome in Stroke Inpatient Rehabilitation: Predicting No, Low and High Response Patients

Abstract: The aims of this study were: (1) to identify reliable prognostic factors for detecting subgroups of no, low and high response in consecutive patients admitted for rehabilitation of first stroke sequelae, and (2) to quantify the relative risk of poor or excellent prognosis on both Activities of Daily Living (ADL) and mobility for each significant variable. We prospectively studied 440 of 475 patients. From a group of 32 independent variables, those significantly associated with no, low and high effectiveness on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
113
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(121 citation statements)
references
References 22 publications
5
113
1
2
Order By: Relevance
“…37 In associating outcomes and hemisphere of lesion, findings have varied with reports that right hemisphere lesions relate to poorer functional outcomes poststroke 11,12 and in rehabilitation units, 38 whereas others report no relationship. [13][14][15] Thus, hemisphere of lesion may not be a good predictor of recovery after stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 In associating outcomes and hemisphere of lesion, findings have varied with reports that right hemisphere lesions relate to poorer functional outcomes poststroke 11,12 and in rehabilitation units, 38 whereas others report no relationship. [13][14][15] Thus, hemisphere of lesion may not be a good predictor of recovery after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,10 Research analyzing outcomes in relation to hemisphere of lesion vary; some studies report that right hemisphere lesions relate to poorer functional outcomes, 11,12 whereas others report no relationship. [13][14][15] Interestingly, studies examining cognitive outcomes after stroke have focused almost entirely on hemisphere of lesion. Generally those with left-side lesions show language and speech disorders, whereas those with right-side lesions show predominantly perceptual and visuospatial deficits.…”
mentioning
confidence: 99%
“…Patients with aphasia often remain disabled despite low baseline NIHSS scores [5]. These patients are increasingly treated with thrombolysis.…”
Section: Introductionmentioning
confidence: 99%
“…The end point was 6 months after stroke as most motor and functional recovery takes place before that time. To enable adjustment for case-mix, several variables were documented based on previous studies of prognostic factors for motor 9 and functional recovery. 6 -8 Age, 6 -9 gender, 8 time between stroke onset and admission assessment, prestroke disability 8 (assessed by BI), type of stroke, side of impairment, urinary incontinence, 6 -8 and swallowing problems 6,7 were recorded on admission.…”
Section: Discussionmentioning
confidence: 99%
“…6 -9 Age, aphasia and initial impairment have been associated with motor recovery. 9 Tilling et al 8 found that the functional recovery of patients admitted for rehabilitation was predicted by urinary incontinence, sex, prestroke disability, dysarthria, age, dysphasia, and limb deficit.…”
mentioning
confidence: 99%